Jīwana britānta Nawāba Kapūra Siṅgha : Khālasā dalāṃ ate misalāṃ dā bānī - Prema Siṅgha, 1882-1950 (SAMP early 20th-century Indian books project ;, 1952)
Biography of Kapūra Siṅgha, Nawab, 1697-1753, Sikh leader.